2022
DOI: 10.21608/puj.2022.169218.1190
|View full text |Cite
|
Sign up to set email alerts
|

The effects of common house fly (Musca domestica) larvaederived substances on wound healing in mouse model

Abstract: Background: Maggot debridement therapy is a therapeutic wound myiasis that depends mainly on L. sericata larva. Owing to its availability and cheap breeding, M. domestica was suggested as an alternative to Lucilia. Objective: The present study was designed to assess the role of M. domestica larvae-derived substances on wound healing in immunocompetent and immunosuppressed mice. Material and Methods: Chitosan and gut extracts, obtained from M. domestica larvae, were applied daily on skin wounds of Swiss albino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…A recent report demonstrated the beneficial use of M. domestica as an alternative to other commonly used larvae in maggot debridement therapy being more available and easier to breed. Moreover, it was confirmed that chitosan which is extracted from the cuticles of larvae was superior in accelerating wound closure [24] .…”
Section: Introductionmentioning
confidence: 92%
“…A recent report demonstrated the beneficial use of M. domestica as an alternative to other commonly used larvae in maggot debridement therapy being more available and easier to breed. Moreover, it was confirmed that chitosan which is extracted from the cuticles of larvae was superior in accelerating wound closure [24] .…”
Section: Introductionmentioning
confidence: 92%